Analysis Of Bottled Drinking Water Productivity At Company XYZ In Bali - Sipayung, Ruth Wenda; I Wayan Gede Sedana Yoga; I Ketut Satriawan (Cita konsultindo, 2025)
XYZ is a company in Bali that is engaged in various product fields, one of which is bottled drinking water. During the operational process, the company faces various challenges such as production fluctuations, machine damage, labor shortages, and defective products, especially in 19-liter gallon bottled water products. These problems have an impact on the company's productivity decline. This study aims to analyze productivity levels using the Production, Organization, Sales, Product, Arbeiter, Capital (POSPAC) method, identify the factors causing the decline in productivity, and develop strategies to improve partial productivity at XYZ. The analysis of the causes of the decline in productivity was conducted using a fishbone diagram, and improvement strategies were proposed to enhance the company's performance. The results of the study show that productivity declined dramatically in certain months. Production productivity in November fell by -1.22%, organizational productivity in July by -8.05 %, sales productivity in December by -17.49%, product productivity in December by -33.95%, labor productivity in September by -32.16%, and capital productivity in December by -57.88%. Factors contributing to the decline in productivity include high absenteeism, employee disputes, machine breakdowns, weak organizational and distribution management, and unstable raw material quality.